Dubichynskyi, Volodymir/ Jaskólski, Adam/ Muszyńska-Wolny, Dorota (2021), Leksykograficzna interpretacja rosyjsko-polskich paraleli frazeologicznych. Warszawa: Wydawnictwo Uniwerystetu Warszawskiego, ss. 237, ISBN 978-83-235-4933-8 - Dźwierzyńska, Ewa (Acta Neophilologica, 2023)
-